Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan pada Perusahaan Sektor Industri yang Terdaftar di BEI Tahun 2019-2022 - Humaira, Shirly; Dwiharyadi, Anda; Djefris, Dedy (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study aims to investigate the influence of the fraud hexagon, comprising stimulus, opportunity, rationalization, capability, arrogance, and collusion, on instances of financial statement fraud within the industrial sector listed on the Indonesia Stock Exchange from 2019 to 2022, involving 48 companies. The components of the fraud hexagon are operationalized as follows: financial targets represent the stimulus, nature of industry proxy for opportunities, auditor changes indicate rationalization, director change signify capabilities, the frequent presence of CEO pictures reflects arrogance, and collaborations with government projects represent collusion. Through purposive sampling, 33 companies meeting specific criteria were selected, resulting in a total of 132 observations. Logistic regression was employed for data analysis, with IBM SPSS 26 used for data processing. The study's findings reveal that financial targets, nature of industry, auditor changes, director change, and the frequency of CEO pictures do not exert influence on financial statement fraud. However, collaboration with government projects is identified as a factor impacting financial statement fraud.